Antioxidant, cytotoxic and DNA protective properties of Achillea eriophora DC. and Achillea biebersteinii Afan. extracts: A comparative study - Maryam Varasteh-kojourian; Parvaneh Abrishamchi; Maryam Matin; Javad Asili; Hamid Ejtehadi; Fatemeh Khosravitabar (Mashhad University of Medical Sciences, 2017)
Objective: Achillea is a traditional medicinal herb which contains different phenol and flavonoid compounds that are responsible for Achillea pharmacological effects. We aimed to determine phenol and flavonoid contents, besides antioxidant activities of different extracts from Achillea eriophoraa (A. eriophora) DC. and Achillea biebersteinii (A. biebersteinii) Afan. (endemic species in Iran) and to investigate their effects on human cells.Materials and Methods: Achillea extracts, were prepared by maceration and shaking methods, from different parts (aerial parts, stem, leaves and inflorescence) of two species using methanol and ethanol as solvents. Total phenol and flavonoid contents were measured by spectrophotometry, and antioxidant activities of the extracts were determined by DPPH radical scavenging, BCB and TBARS assays. Cytotoxicity and antioxidant activities of the extracts were investigated in Human Foreskin Fibroblast (HFF3) cells using MTT, comet and H2O2 assays.Results: Methanol extracts of A. biebersteinii prepared from leaves and inflorescence by maceration method exhibited maximum phenol (1657.58 ± 36.45 mg GAE/100 g DW) and flavonoid (264.00 ± 62.16 mg QUE/100 g DW) contents. Leaf methanol extract showed significantly higher antioxidant activity (0.0276 ± 0.003, 0.16 ± 0.016 and 13.96 ± 0.26 mg/ml for DPPH, BCB and TBARS IC50s, respectively) than those of the other extracts. Leaf extract of A. biebersteinii was not cytotoxic even at the highest examined dose (512 µg/ml) and inhibited cell toxicity induced by H2O2 (98% viability for the cells pretreated with plant extract in the presence of H2O2). Comet assay also confirmed high DNA protective activity of leaf extracts.Conclusion: Achillea extracts possess remarkable antioxidant activity, and could be good natural alternatives to synthetic antioxidants in pharmaceutical and food industries.